Bimbingan Peningkatan Spiritualitas Anak Usia Dini Melaui Metode Kisah Nabi - Ardiansyah Ardiansyah; Inang Raeni; Harfiani Harfiani; Asria Asria (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2022)
Strengthening spirituality in early childhood plays a crucial role in shaping character and moral values for the future. Baubau City, with its rich cultural heritage and strong Islamic traditions, offers a strategic context for implementing spiritual guidance programs for young learners. This Community Service Program (PKM) was conducted at TK Negeri Pembina Kokalukuna in Baubau to provide spiritual guidance for early childhood students. The program employed a storytelling approach, focusing on the exemplary life of the Prophet as a model for cultivating moral values. The findings indicate an improvement in children’s basic understanding of spiritual values, particularly in recognizing the sirah of the Prophet, including his historical legacy and virtuous character. The study recommends collaborative efforts among teachers, parents, and the wider community to strengthen children’s spirituality from an early age.